An exposition of humanistic-existential social work in light of ubuntu philosophy: towards theorizing ubuntu in social work practice - Chigangaidze, Robert K. (Routledge, 2021)
The article stimulates a discourse for theorizing ubuntu as part of a humanistic-existential approach in social work. The article expatiates on the ontologies and axiology of the humanistic-existential approach in light of ubuntu in an effort to theorize the latter through a comparative analysis of the two. Nine features of the humanistic-existential approach are explored: self-awareness, self-determination, human dignity, holism, the pursuit of social justice and human rights, motivation, social cohesion, spirituality, and death. The article calls for theorizing ubuntu philosophy in social work practice and education. It contradicts with other claims that deny ubuntu its place in the humanistic-existential approach.